Increasing Kebon Ayu Village Weaving Business Results Through Product Information Media Online Weaving Product Marketing Training - Uyun, Musmiratul; Syakirin, Syakirin; Ardina, Zety; Kurniawan, Arjun; Purma, M. Raga Al Abtad; Afrianti, Feni (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Kebon Ayu Village is one of the weaving production centers in West Lombok Regency. However, the development is not as significant as other weaving centers on Lombok Island, namely Pringgasela Village, East Lombok Regency, Sukarara and Sade Villages, Central Lombok. October 2023 in Kebon Ayu village illustrates that songket and Bendang weaving in Kebon Ayu village is carried out in each resident's house, the weaver mothers sit on the tumah terrace and in the berugaq in front of the house to finish the woven cloth that is being worked on. The weaving products are marketed through safekeeping to traveling cloth traders to homes and offices in West Lombok and even Mataram. Because of this, we are carrying out community service with the theme of Improving Weaving Results in Kebon Ayu Village through Product Information Media, which includes online marketing training armed with product photos that have been made by service providers. With this service activity It is hoped that this will open up new opportunities for Kebon Ayu Village weavers to develop. With the digitalization of marketing, woven products are no longer only for local needs, such as events make And turn around, but also a superior commodity that is in demand outside Lombok.